2014
DOI: 10.1080/00380768.2014.949853
|View full text |Cite
|
Sign up to set email alerts
|

The changes in physiological and biochemical traits of Tibetan wild and cultivated barley in response to low phosphorus stress

Abstract: Low phosphorus (LP) limits crop growth and productivity in the majority of arable lands worldwide. Here, we investigated the changes in physiological and biochemical traits of Tibetan wild barleys (Hordeum vulgare L. ssp. spontaneum) XZ99 (LP tolerant), XZ100 (LP sensitive), and cultivated barley ZD9 (moderately LP tolerant) under two phosphorus (P) levels during vegetative stage. These genotypes showed considerable differences in the change of biomass accumulation, root/shoot dry weight ratio, root morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…However, the reduction varied among genotypes and the genotypes with comparatively less reduction were considered as P-efficient genotypes, such as Xinluzao-49 and Xinluzao-48. In line with the current findings, lowered root and shoot P concentrations and accumulation were observed in barley under low P concentrations [33]. Under P-deficient conditions, most of the P is translocated into leaves in P-efficient genotypes as described previously [41].…”
Section: Variation and Classification Of Cotton Genotypes For P Use Esupporting
confidence: 91%
See 2 more Smart Citations
“…However, the reduction varied among genotypes and the genotypes with comparatively less reduction were considered as P-efficient genotypes, such as Xinluzao-49 and Xinluzao-48. In line with the current findings, lowered root and shoot P concentrations and accumulation were observed in barley under low P concentrations [33]. Under P-deficient conditions, most of the P is translocated into leaves in P-efficient genotypes as described previously [41].…”
Section: Variation and Classification Of Cotton Genotypes For P Use Esupporting
confidence: 91%
“…Moreover, the increase in P acquisition in P-efficient genotypes might be due to an increase in the root absorption area, which may also affect the ability of plants to acquire nutrients from the medium [32]. The increase in root morphological traits under P-deficient conditions was also noted in other crops [33,34]. In the current study, increased root length and surface area were observed in Xinluzao-49 and consequently the root and shoot biomass were increased significantly as compared to other cotton genotypes.…”
Section: Variation In Morphological and Physiological Traitsmentioning
confidence: 94%
See 1 more Smart Citation
“…P deficiency can alter the metabolism and translocation of carbohydrates, such as soluble sugars and organic acids [ 5 , 20 22 ]. Increased accumulation of carbohydrates, especially sucrose, was observed in leaves of many plant species under P deficiency [ 5 , 23 26 ], which was attributed to low sink demand and limited leaf expansion under P starvation [ 12 , 27 ]. Secretion of organic acids is one of the most important low-P responses in plants, which dissolves soil P via acidification and complexation, and confers differing levels of low-P tolerance in crops [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barley (Hordeum vulgare L.) is one of the principal cereal crops all over the world (Consortium 2012;Nadira et al 2014). It is used as forage and grain as well as a health food.…”
Section: Introductionmentioning
confidence: 99%